Alcohol consumption among adult males in urban area of Thanlyin Township, Yangon Region, Myanmar - Oo, Win Myint; Aung, May Soe; Soe, Pa Pa; Lwin, Su Htar; Win, Myat Ohnmar (International Journal of Research in Medical Sciences, 2017)
Background: Alcohol consumption is a major cause of morbidity and mortality worldwide. It is frequently related to health and behavioural problems as well as socio-economic hardship. Therefore, this study was conducted to determine the prevalence and risk factors of alcohol consumption among adult males residing in urban area of Thanlyin Township, Yangon Region. Methods: A cross-sectional study was conducted among 380 adult males. Multi-stage random sampling was applied. Data entry and analysis was done using Stata 11.0 statistical package. Results: The prevalence of current alcohol drinking, ex-drinking and never drinking were 20.5%, 9.0% and 70.5%, respectively. There was a significant decreasing trend of alcohol consumption across the levels of age-group. Age, education status and practicing other health-risk behaviours such as smoking and betel chewing were detected as significant risk factors of alcohol consumption. Ever smokers and ever betel chewers were about 4 times more likely to be ever alcohol user compared to their counterparts even if age and education level were adjusted. By controlling smoking and betel chewing habits, 79.2% and 76.6% of existing prevalence of alcohol consumption among respondents would be reduced, respectively. Conclusions: There is an urgent need to curb the habit of alcohol consumption among adult males living in urban area, especially young adults. Alcohol and tobacco control policies in Myanmar should be strengthened or reinforced. Tobacco control program also needs to be intensified. Health education and health promotion activities should be enhanced in order to reduce alcohol consumption in the country.